Insta-Inspiration: The Influence of Celebrities’ Instagram Accounts on The Consumptive Behavior of Youths - Steven Christovery; Yenny Purwati (Jurnal Akuntansi dan Pajak, 2023)
This study aims to discuss the effect of teenagers’ motivation for following celebrities’ Instagram accounts on consumptive behavior and the effect of parasocial interaction as a moderating variable as well as social identity as a mediation variable. The research employs a quantitative approach and the study data were collected through an online survey. The purposive sampling technique was selected for this research with the sample of 120 respondents. Respondents’ criteria for this study include teenagers aged 15-17 who are fans and followers of NCT Dream’s Instagram account. To process the data from the online survey, moderated regression analysis (MRA) and Hayes model 4 were carried out. The results showed that there are significant effects of motivation for following celebrities’ Instagram accounts on teenagers’ social identity and consumptive behavior. Furthermore, MRA demonstrates that parasocial interaction strengthens the moderation effect of teenagers’ motivation for following celebrities’ Instagram accounts on consumptive behavior. In addition, Hayes model 4 shows that social identity mediates the effect of teenagers’ motivation for following celebrities’ Instagram accounts on consumptive behavior.